Analysis of BOS Fund Efficiency in Senior High Schools: A Case Study in DKI Jakarta - Akbari, Alfian Fery; Wijayanti, Nanda Ayu (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study uses a mixed-method approach, combining quantitative Data Envelopment Analysis (DEA) and qualitative interviews to analyze the efficiency of managing school operational assistance funds (Dana BOS) at the senior high school (SMA) level by the Provincial Government of the Special Capital Region (DKI) of Jakarta. DEA is employed to measure fund efficiency using relevant input-output variables, while qualitative interviews contextualize the results. The input variables include the number of students, the number of teachers, the total BOS budget, and the remaining budget surplus (SiLPA). Meanwhile, the output variables consist of national assessment scores in literacy, numeracy, and character, as well as school accreditation levels. The findings reveal varying levels of efficiency across schools. While some manage funds effectively, others show suboptimal use, primarily due to weak planning and misallocation. These insights inform policy recommendations to enhance BOS fund utilization and educational quality